Analysis of a robust implicit scheme for space–time fractional stochastic nonlinear diffusion wave model - Singh A.P.; Maurya R.K.; Singh V.K. (My University, 2025)
The current paper develops and analyzes a numerical scheme for the space–time fractional stochastic nonlinear diffusion wave equations. The implicit scheme is based on the matrix transform technique for discretizing the Riesz-space fractional derivative, (Formula presented.) -order approximation to the Caputo-fractional derivative in time and Taylor's series method to linearize the nonlinear source term, and has been successfully applied to solve a class of nonlinear fractional diffusion wave equation. We prove that the implicit scheme is convergent with β-order in space and (Formula presented.) order in time, respectively. The optimum error estimates in the temporal-spatial direction and unconditional stability of the implicit scheme have been theoretically investigated. Moreover, several specific numerical experiments confirm the consistency and high efficacy of the provided algorithms, which minimizes the computational costs. © 2023 Informa UK Limited, trading as Taylor & Francis Group.